Prognostic Evaluation of Vimentin Expression in Correlation with Ki67 and CD44 in Surgically Resected Pancreatic Ductal Adenocarcinoma. (22nd March 2017) - Myoteri, Despoina; Dellaportas, Dionysios; Lykoudis, Panagis M.; Apostolopoulos, Alexandros; Marinis, Athanasios; Zizi-Sermpetzoglou, Adamantia
Abstract : Purpose. Radical surgical resection with adjuvant chemotherapy or chemo-radiotherapy is the most effective treatment for pancreatic ductal adenocarcinoma (PDAC). However, relatively few studies investigate the prognostic significance of biological markers in PDAC. This study aims to look into the expressions of vimentin, Ki67, and CD44 in PDAC surgical specimens and their potential prognostic implications in survival. Method. The study was designed as retrospective, and vimentin, Ki67, and CD44 expressions were evaluated by immunohistochemistry in 53 pancreatic ductal adenocarcinoma cases. Overall survival was assessed by the Kaplan–Meier method. Results. Patients' median age was 68 years. The median survival was 18 months. The tumors were T3-4 in 40/53 (75.5%), and metastases in lymph nodes were found in 42 out of 53 (79.2%) cases. On multivariate analysis, the size of primary tumor (p < 0.001 ), the surgical resection margin status (p = 0.042 ), and vimentin expression (p = 0.011 ) were independently correlated with overall survival. Conclusions. Long-term survival after resection of PDAC is still about 15%. Vimentin expression is a potential independent adverse prognostic molecular marker and should be included in histopathological reports. Also, CD44 expression correlates with high Ki67, vimentin positivity, and N stage and may represent a potential target of novel therapeutic modalities in pancreatic adenocarcinoma patients.